Influence of Zika virus 3′-end sequence and nonstructural protein evolution on the viral replication competence and virulence. Issue 1 (31st December 2022) - Jung, Hae-Gwang; Cho, Hee; Kim, Minwoo; Jung, Haewon; Bak, Yeonju; Lee, Se-Young; Seo, Han Young; Son, Yu-Min; Woo, Hawon; Yoon, Gone; Kim, Seong-Jun; Oh, Jong-Won
ABSTRACT: Zika virus (ZIKV) has been circulating in human networks over 70 years since its first appearance in Africa, yet little is known about whether the viral 3′-terminal sequence and nonstructural (NS) protein diverged genetically from ancient ZIKV have different effects on viral replication and virulence in currently prevailing Asian lineage ZIKV. Here we show, by a reverse genetics approach using an infectious cDNA clone for a consensus sequence (Con1) of ZIKV, which represents Asian ZIKV strains, and another clone derived from the MR766 strain isolated in Uganda, Africa in 1947, that the 3′-end sequence –UUUCU-3′ homogeneously present in MR766 genome and the –GUCU-3′ sequence strictly conserved in Asian ZIKV isolates are functionally equivalent in viral replication and gene expression. By gene swapping experiments using the two infectious cDNA clones, we show that the NS1–5 proteins of MR766 enhance replication competence of ZIKV Con1. The Con1, which was less virulent than MR766, acquired severe bilateral hindlimb paralysis when its NS1–5 genes were replaced by the counterparts of MR766 in type I interferon receptor (IFNAR1)-deficient A129 mice. Moreover, MR766 NS5 RNA-dependent RNA polymerase (RdRp) alone also rendered the Con1 virulent, despite there being no difference in RdRp activity between MR766 and Con1 NS5 proteins. By contrast, the Con1 derivatives expressing MR766 Nsps, like Con1, did not develop severe disease in wild-type mice treated with an IFNAR1 blocking antibody. Together, our findings uncover an unprecedented role for ZIKV NS proteins in determining viral pathogenicity in immunocompromised hosts.